A UWB bidirectional rectangular ring antenna fed by CDM with a rod and ridges for constant beam direction - Vongsack, S.; Lamultree, S.; Osklang, P.; Phongcharoenpanich, C.; Kosulvit, S.; Hamamoto, K.; Wakabayashi, T. (My University, 2012)
This paper presents an ultra-wideband (UWB) rectangular ring antenna excited by a circular disc monopole (CDM) with a conducting rod and two double ridges to radiate bidirectional pattern with constant beam direction along the entire UWB frequency range of 3.1-10.6GHz. The conducting rod and double ridges at the upper wall of the ring are added to solve the tilted beam problem at the higher edge frequency whereas the double ridges at the lower wall are used to enhance the impedance bandwidth. The dimensions of the rectangular ring and the CDM are initially considered to achieve the bidirectional pattern with the suitable resonant frequencies and bandwidth. Then, the parameters of copper rod and two double ridges are determined by parametric study using CST Microwave Studio simulation software. The prototype antenna was fabricated, and the measured results show good agreement with the simulated ones. The obtained bandwidth of |S 11| < - 10 dB can cover the UWB frequency range as well as the bidirectional beam radiation with constant beam direction (θ = 0°, 180° and φ = 90°). The minimum and maximum measured gains are 3.1dBi to 5.3dBi, respectively. The proposed antenna possesses compact size with good radiation performance that can be a promising candidate for UWB applications. Copyright © 2012 S. Vongsack et al.